The Rise of the Loss and Damage Fund in a Fragmented International Political Landscape - Halim, Abdul; Aisyah, Sari Mutiara; Setiawan, Roy (Universitas Riau Kepulauan, 2026)
This study examines the international political dynamics and power asymmetries that shaped the negotiation and institutionalization of the Loss and Damage Fund (LDF) under the UNFCCC framework. While loss and damage has historically been marginalized within global climate governance, its elevation at COP27 reflects a significant shift driven by contestation between developed and developing countries. The research integrates historical institutionalism and Global South dependency theory to analyze how institutional legacies, path-dependent mechanisms, and structural inequalities have influenced the design and operationalization of the LDF. Methodologically, this study employs a qualitative-explanatory, process-tracing approach to capture the evolution of negotiations and institutional outcomes. Data are drawn from systematic analysis of UNFCCC negotiation texts, official COP decisions, and policy reports. The findings demonstrate that early institutional design choices shaped by the normative and financial dominance of developed countries generated path-dependent constraints that limited the redistributive and justice-oriented potential of the LDF. However, Global South actors exercised strategic agency by reframing loss and damage as a moral and political issue grounded in historical responsibility, rather than a purely technical concern. Through coalition diplomacy, discursive contestation, and procedural resistance, these actors were able to secure formal recognition of irreversible climate harm within the UNFCCC regime. This study advances climate justice scholarship by offering a theoretically integrated explanation of how structurally disadvantaged actors can reshape institutional outcomes within an unequal global governance system. The LDF thus emerges not merely as a financial mechanism, but as a contested site of institutional transformation, where future effectiveness will depend on governance arrangements, equitable access, and sustained political negotiation.